If you give a dog a donut - Numeroff, Laura Joffe; Bond, Felicia (New York : Balzer + Bray, 2011)
Simple text and illustrations describe the chaos that might ensue if a dog was given a donut.
"An If you give ... book"--Cover.
School Library Journal, October 2011
Publisher's Weekly, August 2011
1.8
K-3
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Dogs -- Fiction; Picture books for children